Regulation of Adipocyte Lipolysis by TSH and its Role in Macrophage Inflammation - Durand, Jason AJ (Université d'Ottawa / University of Ottawa, 2012)
Elevated Thyroid-Stimulating Hormone (TSH) is associated with an increased risk of cardiovascular disease (CVD). We hypothesized that TSH-stimulated FA release from adipocytes contributes to macrophage inflammation. 3T3-L1 and human subcutaneous differentiated adipocytes were treated with TSH for 4 hours under various conditions and lipolysis assessed via glycerol secretion. Optimal conditions were determined and protein expression of ATGL, HSL and perilipin remained stable. TSH-stimulated 3T3-L1 or human adipocyte-conditioned medium (T-ACM) was placed on murine J774 or human THP-1 macrophages, respectively, and macrophage cytokine mRNA levels (IL-1β, IL-6, MCP-1, and TNFα) were measured by real-time RT-PCR. T-ACM did not change cytokine mRNA expression in J774 macrophages or THP-1 macrophages when compared to ACM. Absence of BSA in the medium may have hindered release of FA from differentiated adipocytes into the medium, BSA may be required to permit adequate FA accumulation in the medium to then evaluate the effect of T-ACM on macrophages. Further investigation is required to determine the effect of FA on J774 and THP-1 inflammatory response.
Keywords: Adipocyte; Lipolysis; Macrophage; subclinical hypothyroidism; cardiovascular disease; TSH; thyroid-stimulating hormone; inflammation; cytokine